Evaluation of Physicochemical Properties of a New Calcium Silicate–based Sealer, Bio-C Sealer - Zordan-Bronzel, Cristiane Lopes [UNESP]; Esteves Torres, Fernanda Ferrari [UNESP]; Tanomaru-Filho, M. [UNESP]; Chávez-Andrade, Gisselle Moraima [UNESP]; Bosso-Martelo, Roberta; Guerreiro-Tanomaru, Juliane Maria [UNESP] (Elsevier, 2019)
Introduction: Calcium silicate–based materials have been proposed as root canal sealers for root canal treatment. The aim of this study was to evaluate the physicochemical properties of a new calcium silicate–based sealer (Bio-C Sealer; Angelus, PR, Brazil) compared with a calcium silicate endodontic sealer (TotalFill BC Sealer; FKG Dentaire SA, La Chaux-de-Fonds, Switzerland) and an epoxy resin sealer (AH Plus; Dentsply DeTrey, Konstanz, Germany). Methods: The setting time and flow were evaluated based on ISO 6876 standard. The pH value was evaluated after different time intervals of storage in deionized water (1, 7, 14, and 21 days). Radiopacity was evaluated by radiographic analysis in millimeters of aluminum. Solubility and volumetric change were evaluated after 30 days of immersion in distilled water. Solubility was assessed by mass loss (%), and volumetric change was evaluated by micro–computed tomographic imaging. The data were submitted to analysis of variance and Tukey statistical tests (P < .05). Results: TotalFill BC Sealer and Bio-C Sealer were similar regarding radiopacity, volumetric change, and pH values (P > .05). Bio-C Sealer presented the shortest setting time and the highest flow and solubility (P < .05). AH Plus showed the highest radiopacity and the lowest flow, pH, solubility, and volumetric change (P < .05). Conclusions: Bio-C Sealer showed a short setting time, alkalinization ability, and adequate flow and radiopacity as well as low volumetric change. However, this sealer had higher solubility than the rates required by ISO 6876 standard.
Keywords: Calcium silicate; endodontics; micro–computed tomography; physicochemical properties; root canal sealer